Islam Answers to the Environmental Crisis: Green Economy in Islamic Perspective - DHANURENDRA, Bagas (Integration: Journal Of Social Sciences And Culture, 2023)
Purpose:In this paper, we will discuss how to interpret Green Economy concepts and policies within the framework of Islamic environmentalism, one of which is by using the thoughts of Seyyed Hossein Nasr. Methodology:The approach in research that the author uses is a qualitative approach, a scientific and systematic method to conduct and study an object without manipulation and hypothesis testing. At the same time, the form of research that the author will carry out is a form of library research. Findings:Amid this complicated problem, Seyyed Hossein Nasr offers a solution: As a Modern Man, he must place the universe (cosmos, both macro and micro) as a theophany. It means that modern society needs to re-establish its understanding of the existence of self, nature, and God and how their relationship can be harmonious. Implication:Seyyed Hossein Nasr invites us to reflect that human essence is integral to nature through this the-centrism framework. At the same time, the universe is a reflection of Divine power.